Current Status and the Future of Occupational Safety and Health Legislation in Low- and Middle-Income Countries - Ncube, France (Saf Health Work, 2018)
This article addresses three key issues. First, the commonalities, differences, strengths, and limitations of existing occupational safety and health (OSH) legislation of low- and middle-income countries were determined. Second, required revisions were identified and discussed to strengthen the laws in accordance with the best international practice. Finally, proposals for additional OSH laws and interventions were suggested. A literature search of OSH laws of 10 selected low- and middle-income countries was carried out. The laws were subjected to uniform review criteria. Although the agricultural sector employs more than 70% of the population, most of the reviewed countries lack OSH legislation on the sector. Existing OSH laws are gender insensitive, fragmented among various government departments, insufficient, outdated, and nondeterrent to perpetrators and lack incentives for compliance. Conclusively, the legal frameworks require reformation and harmonization for the collective benefit to employees, employers, and regulatory authorities. New OSH legislation for the agricultural sector is required.